Outcomes following transaortic septal myectomy in hypertrophic cardiomyopathy - Kummari, Madhusudan; Malempati, Amaresh Rao; Gopal Palanki, Surya S.; Bomma, Kaladhar (International Surgery Journal, 2020)
Background: The objective of the study was to evaluate effect of myectomy and its impact on survival for a period of one year and to identify the co-morbid conditions that would increase the risk of surgery. Methods: The study was conducted on the patients admitted in a single unit of department of cardiothoracic surgery, NIMS, Hyderabad during the period of 2014 to 2018. The study was a retrospective observational study. 21 patients were enrolled in the study after approval from institute ethics committee. All the patients between 7 to 70 years who underwent septal myectomy were included in the study. Results: Out of the 21 patients underwent modified Morrows myectomy 16 (76.2%) were male and 5 (23.8%) were female. The most common presenting symptom was dyspnea (81%), followed chest pain (76%), palpitations (62%) and syncope (38%). 5 (24%) patients had a family history of sudden cardiac death. Preoperative beta blockers were used by 15 (72%) patients. 11 patients had severe mitral regurgitation, out of which 8 patients underwent valve replacement and 3 underwent mitral valve repair. The mean preoperative left ventricular outflow tract obstruction gradient was 86.86 and the mean postoperative gradient was 23.47. 3 patients had implantable cardioverter defibrillator insertions. All patients had symptom relief. Conclusions: Surgical treatment of hypertrophic cardiomyopathy through transaortic septal myectomy is safe and effective method to relieve left ventricular outflow tract obstruction. Mitral valve replacement can be done for cases with structural defect of mitral valve. Early detection and intervention in patients with family history of sudden cardiac death would reduce the risk of death and ensure long term survival.